Infestation By Leucoptera coffeella and leaf levels of total soluble sugar and protein in organic coffees - Theodoro, Vanessa Cristina de Almeida; Guimarães, Rubens José; Mendes, Antonio Nazareno Guimaraes (Coffee Science - ISSN 1984-3909, 2014)
The experiment was conducted in August 2004 in a coffee plantation, cultivar Catuaí Amarelo, area of 4.0 x 0.7 m and age of 6) in the first year of agroecological transition. Experimental design used was the lattice balanced 4x4 with five replications in factorial scheme 3x2x2 and four more additional treatments. Sixteen treatments were tested according to the standards of organic agriculture: three organic fertilizers (castor bean bran, bovine manure, boiler litter), with or without straw of fermented coffee applied on fertilizers, with or without green manure Cajanus cajan L. between the coffee’s line, and foliar fertilization with biofertilizer for all organic treatments. Additional treatments tested the effect of the use of coal and rock flour together with organic fertilizers and only use straw of fermented coffee and green manure as fertilizer. The conventional management (control) used ammonium sulfate, potassium chloride and conventional foliar fertilization. We evaluated the interaction between the behavior of the coffee leaf miner (Leucoptera coffeella) on the content of total soluble sugars and protein in leaf coffee. It was found that the organic fertilization affects the production of soluble sugars in the leaf of coffee, since conventional fertilization needs further studies in tropical soils. The castor bean bran promotes a lower accumulation of soluble sugars in the leaf, which possibly contributes to an increase in plant resistance to coffee leaf miner.